Contact angle & bearing selection for high speed grease lubricated spindles - Moratz, William; Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2003)
This program focuses on grease lubrication of spindle bearings, high speed spindle analysis, selecting optimum contact angle and bearing materials, state of the art HNS race material technology, ceramic hybrid bearing technology, and spindle performance gain potential
Code no : DV03PUB82
Recorded at the High Speed Machining Technical Conference, Apr. 8 & 9, 2003, Itasca, Ill.
Title from title screen
Presenter: William Moratz
Keywords: Lubrication and lubricants; Bearings (Machinery); Lubrication systems; Spindles (Machine-tools)